Analisis Uji Sensori dan Kandungan Gizi Gyoza Substitusi Ikan Tuna Dengan Penambahan Daun Kelor Sebagai Snack untuk Remaja Putri Anemia Defisiensi Besi - Siti Uswatun Hasanah; Rita Ismawati (Lembaga Pengembangan Kinerja Dosen, 2025)
Adolescent girls are the most vulnerable group to iron deficiency during growth and menstruation. An innovative snack product gyoza substituted with tuna and added moringa leaves can be developed to increase protein and iron content. This study aimed to determine the effect of tuna substitution and moringa leaf addition on sensory evaluation of gyoza’s color, aroma, texture, and taste as a snack for adolescent girls with iron deficiency anemia. The research is a pure experimental research with a completely randomized design. The sensory test data collection technique was carried out on 35 untrained panelists. The 4 formulations developed, namely F1 (25g tuna substitution with the addition of 10g moringa leaves), F2 (50g tuna substitution with the addition of 10g moringa leaves), F3 (75g tuna substitution with the addition of 10g moringa leaves), and F4 (100g tuna substitution with the addition of 10g moringa leaves). Then it was analyzed using the Kruskal Wallis test and the Mann-Whitney test as a further test. The results of the four formulations showed that there was an effect of tuna substitution with the addition of moringa leaves on the texture and taste sensory test however, there was no effect of tuna substitution with the addition of moringa leaves on the color and aroma sensory test and the best product was obtained in F3. The results of the gyoza nutritional content test that was substituted with tuna and the addition of the best moringa leaves or F3 formula based on laboratory testing had a nutritional content of 11,25% protein and 0,022% iron per 100 grams of gyoza. It is hoped that further research will modify the amount of moringa leaves added to improve the organoleptic test of gyoza products by panelists and examine gyoza formulations for other nutritional content that has not been tested and economic value.